2021
DOI: 10.1039/d0cp06073a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of 11B solid-state NMR parameters of boron-rich compounds II: the orthorhombic phases MgB7 and MgB12C2 and the boron modification γ-B28

Abstract: After referencing 11B NMR spectra for molecular icosahedral boranes and the subsequent transfer to boron-rich borides of the α-rB12 type, we show that NMR spectra of borides with four or five symmetry-independent boron atoms can also be calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…40 Quite recently, the main group metal doped-boron clusters have received a great deal of attention. [41][42][43][44][45][46] It has been shown that Li atoms can stabilize the smallest double-ring boron tube of Li 2 B 12 , 44 or triplering boron tube in Li 2 B 24 . 47 In addition, a planar B 7 wheel can be incorporated in a sandwich-like structure between Li-and Na-based subunits.…”
Section: Introductionmentioning
confidence: 99%
“…40 Quite recently, the main group metal doped-boron clusters have received a great deal of attention. [41][42][43][44][45][46] It has been shown that Li atoms can stabilize the smallest double-ring boron tube of Li 2 B 12 , 44 or triplering boron tube in Li 2 B 24 . 47 In addition, a planar B 7 wheel can be incorporated in a sandwich-like structure between Li-and Na-based subunits.…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of bonding situations can be explained and therefore interpreted in relation to physical properties. [21][22][23][24][25][26][27][28] In this work, we highlight on chemical bonding of the C, N and O local structures in Silicon bulk and in Silicon GB Σ3{111} with and without vacancies. In order to understand the organization and the underlying electronic structure of the inclusion of C, O and N atoms in Si structures, we focus on topological analysis obtained from density distribution.…”
Section: Introductionmentioning
confidence: 99%
“…We present the characteristics of electron localization function (ELF) obtained from firstprinciples calculations. [19][20][21] ELF analysis contribute to the understanding of the behavior and properties of C, N and O atoms in Silicon structures by the characterization of the chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach, increasingly popular for crystalline systems in the past decade, is the analysis of the chemical bonding based on the topological analysis obtained from density distribution. In particular, electron localization function (ELF) [19][20][21] has emerged as a powerful tool to understand the behavior of the electrons in atoms, molecules and solids. A great variety of bonding situations can be explained and therefore interpreted in relation to physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of bonding situations can be explained and therefore interpreted in relation to physical properties. [21][22][23][24][25][26][27][28] In this work, we highlight chemical bonding of the C, N and O local structures in silicon bulk and in silicon GB S3{111} with and without vacancies. In order to understand the organization and the underlying electronic structure of the inclusion of C, O and N atoms in Si structures, we focus on topological analysis obtained from density distribution.…”
Section: Introductionmentioning
confidence: 99%